Not just about pills: Findings from a national survey of pharmacists to understand their views on addressing social determinants of health - Katherine A. Meehan; Austin R. Waters; Mary Wangen; Olufeyisayo O. Odebunmi; Renée M Ferrari; Macary W. Marciniak; Alison T. Brenner; Stephanie B. Wheeler; Parth D. Shah (Preventive Medicine Reports)
Objective: We evaluated community pharmacists' perspectives on addressing social determinants of health for their patients in the United States. Methods: From 9/2022—1/2023, we conducted a national, online survey of 578 pharmacists to evaluate their perspectives on social barriers affecting their patients, their pharmacy staff's ability to address these social barriers, and resources available or needed to address barriers. Results: Healthcare access and quality was perceived as the most addressable social barrier (59 %), while education (24 %) and neighborhood/built environment were perceived as the least addressable (14 %). Staff capacity to address social needs was significantly associated with increases in the pharmacy's ability to address social determinants of health across all five domains. Pharmacists were more likely to report adequate staff capacity if they practiced in independent community pharmacies. Conclusions: Pharmacists commonly address social determinants of health of their patients, but most lack adequate staff capacity to address patient social barriers. Pharmacies with capacity can only address a portion of the social needs of their patient population. Greater access to resources and staffing support are needed to improve pharmacy's role in addressing patient unmet social needs.